Overexpression of Transketolase Relieves xylA Repression and Enhances Xylose Utilization in Saccharomyces cerevisiae During Mixed Sugar Fermentation - Si Xu; Wanli Cheng; Huanan Li; Jiashu Liu; Kexin Chen; Zhengbing Jiang (GCB Bioenergy)
ABSTRACT Metabolic engineering of Saccharomyces cerevisiae has enabled xylose‐fermenting yeast strains. However, the bioavailability dilemma of xylose has become the core bottleneck restricting the economy of lignocellulose. This study investigates the overexpression of the transketolase gene (TKL1) in the pentose phosphate pathway to enhance xylose utilization efficiency during mixed sugar fermentation. We initially characterized the effects of different carbon and nitrogen sources on xylose consumption and ethanol production. The recombinant yeast strain INVSc‐xylA‐Xltr1p‐TKL1 demonstrated significant improvements in xylose utilization. In a xylose‐only medium (SCX) with organic nitrogen, the strain consumed 1.54 g/L of xylose over 120 h, while in a mixed glucose and xylose medium, xylose consumption reached 3.01 g/L, reflecting increases of 52.4% and 16.2% compared with the control, respectively. With inorganic nitrogen, the strain consumed 1.3 g/L of xylose in a SCX medium and 2.69 g/L in a mixed glucose‐xylose medium, corresponding to increases of 13% and 24.5% compared with the control group, respectively. Under optimal conditions, the recombinant strain achieved a sugar‐to‐ethanol conversion rate of 0.43 g/g, yielding 84.3% and 93.5% of the theoretical ethanol production for glucose and xylose, respectively. Furthermore, qPCR analysis revealed that the expression level of the xylose isomerase (xylA) gene in INVSc‐xylA‐Xltr1p‐TKL1 was significantly upregulated, doubling that of the control. This enhanced expression correlated with reduced xylulose accumulation, suggesting alleviation of xylA repression. These findings demonstrate that transketolase overexpression enhances the co‐utilization of glucose and xylose, improving bioethanol production efficiency.